Faktor-Faktor yang Mempengaruhi Penyerapan Tenaga Kerja Sektor Basis di Provinsi Bali - Medah, Ginda Jenifa; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 3, Maret 2017 (pp. 286-471), 2017)
This study aimed to determine (1) what are the sectors that are classified as the basic sector of the economy of Bali Province in the period 2000-2015; (2) how the trends / tendency of employment in the sector and the non-base basis in Bali during the period 2000-2015; (3) how the influence of sector GDP basis, the minimum wage and government expenditure on employment sector in the province of Bali basis during the period of 2000-2015. The data in this study were collected by recording from CPMs and the Regional Office Bali Province of revenues from 2000 to 2015 for all variables. Analysis of the data used in this study is Location Quotient (LQ) and Shift Share analysis (SS) and to determine the effect on employment sector basis used OLS Regression. Based on the survey results revealed that (1) sectors that are classified as a sector basis in Bali Province in the period 2000-2015 is electricity, gas and water supply, trade, hotels and restaurants and transport and communications; (2) Employment in the sector and the non-base basis in Bali Province in the period 2000-2015 has increased significant; (3) The sector GDP basis, minimum wages and government spending and a significant positive effect on employment sector in the province of Bali basis during the period of 2000-2015.
Keywords: PDRB, upah minimum, pengeluaran pemerintah, penyerapan tenaga kerja